2021
DOI: 10.1186/s12913-021-06444-x
|View full text |Cite
|
Sign up to set email alerts
|

What if something happens tonight? A qualitative study of primary care physicians’ perspectives on an alternative to hospital admittance

Abstract: Background Due to demographic changes, hospital emergency departments in many countries are overcrowded. Internationally, several primary healthcare models have been introduced as alternatives to hospitalisation. In Norway, municipal acute wards (MAWs) have been implemented as primary care wards that provide observation and medical treatment for 24 h. The intention is to replace hospitalisation for patients who require acute admission but not specialist healthcare services. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Thus, the MAW appears to represent an intermediate unit rather than an alternative to the hospital. This is supported by studies claiming that the MAW represents an additional health service to already existing services [ 12 , 14 , 19 ]. Originally, the intention of the MAW was to establish an alternative to hospitalisation, particularly suitable for patients with a clarified condition or an acute deterioration of an already known condition.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, the MAW appears to represent an intermediate unit rather than an alternative to the hospital. This is supported by studies claiming that the MAW represents an additional health service to already existing services [ 12 , 14 , 19 ]. Originally, the intention of the MAW was to establish an alternative to hospitalisation, particularly suitable for patients with a clarified condition or an acute deterioration of an already known condition.…”
Section: Discussionmentioning
confidence: 84%
“…The extended diagnostics in hospital was used for one out of ten patients. The extended diagnostics service has become a better-known opportunity for clinicians to ensure that patients admitted to the MAW receive the right diagnosis; that is, the use of X-rays, laboratory tests and specialist assessment by hospital physicians are assumed to give the patients a more clarified diagnosis [ 7 , 12 ]. However, most patients in MAWs are old, with a high degree of frailty [ 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…nurses, physicians), a division between specialist and generalist services (e.g. two governmental levels), as well as an uncertainty related to who is responsible for the patient [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have explored primary healthcare professionals’ perspectives on older patients’ pathways within the healthcare system [ 21 , 25 , 26 ]. A qualitative study that included primary care nurses’ and hospital physicians’ perspectives on the transition from hospital to home concluded that effective communication between professionals across different healthcare institutions and different governmental levels is essential to reduce the readmission rate and improve safety and continuity of care [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…were forced to require GP referral to specialist healthcare services [1]. Patients in Norway who needed acute treatment but not specialty care were even transferred by primary care physicians to municipal acute wards as an alternative to hospitalization [2]. In other countries such as Japan, though patients are not forced to register with a general practitioner or family doctor, they should pay additional costs if bypassing primary care physicians and receiving care in higher-level facilities [3].…”
Section: Introductionmentioning
confidence: 99%